2017
DOI: 10.1111/1365-2664.12991
|View full text |Cite
|
Sign up to set email alerts
|

Weed suppression greatly increased by plant diversity in intensively managed grasslands: A continental‐scale experiment

Abstract: Grassland diversity can support sustainable intensification of grassland production through increased yields, reduced inputs and limited weed invasion. We report the effects of diversity on weed suppression from 3 years of a 31‐site continental‐scale field experiment.At each site, 15 grassland communities comprising four monocultures and 11 four‐species mixtures based on a wide range of species' proportions were sown at two densities and managed by cutting. Forage species were selected according to two crossed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 41 publications
(85 reference statements)
7
50
2
Order By: Relevance
“…Reduced weed biomass in intercropping systems has been reported by several workers for cereal-grain legume [21], for pea-barley [22], for maize-legume [23], and for maize-faba bean [24]. These studies confirmed that species diversity maintains a highly asymmetric competition over weeds [25], but these relations still need to be investigated in further detail and compared with the effects of other agronomic options of weed control, e.g., increased seed density or mulching. Other studies have reported that species identity (species performance in a particular ecosystem function) outweighs the effect of species diversity on weed suppression [26,27].…”
Section: Introductionsupporting
confidence: 70%
“…Reduced weed biomass in intercropping systems has been reported by several workers for cereal-grain legume [21], for pea-barley [22], for maize-legume [23], and for maize-faba bean [24]. These studies confirmed that species diversity maintains a highly asymmetric competition over weeds [25], but these relations still need to be investigated in further detail and compared with the effects of other agronomic options of weed control, e.g., increased seed density or mulching. Other studies have reported that species identity (species performance in a particular ecosystem function) outweighs the effect of species diversity on weed suppression [26,27].…”
Section: Introductionsupporting
confidence: 70%
“…Weed control in sainfoin can be achieved (Mora-Ortiz, 2015;Malisch et al, 2017) through appropriate choice of partner species, sowing densities, and cutting frequencies and can lead to stable sainfoin percentages (i.e., ~40% of the sward was sainfoin), which suffice to reduce the incidence of bloat (Wang et al, 2006;Malisch et al, 2017). This was also demonstrated for several other legume species in a Pan-European experiment (Finn et al, 2013;Connolly et al, 2017;Suter et al, 2017). Other strategies for weed control can include application of preemergence, postemergence, and maintenance herbicides (Sheldrick and Thomson, 1982;Moyer et al, 1990;Frame et al, 1998;Amiri et al, 2013;Mora-Ortiz, 2015).…”
Section: Weed Controlmentioning
confidence: 87%
“…The management of these grasslands is becoming more complex, as the traditional interests of production and profit optimization are increasingly complemented by concerns about sustainability and provision of ecosystem services and functions 1,47,48 . Previous studies showed the positive impact of plant diversity on many of these ecosystem services and functions in grasslands [49][50][51][52][53][54] . In our study we found additionally substantial economic benefits, in terms of revenues, from higher plant diversity.…”
Section: Management Effectmentioning
confidence: 98%